Factors Associated with Alcohol Consumption among Senior High School Students in Suphan Buri Province, Thailand: A Cross-Sectional Study - Porntipa Amnamorn; Panjarut Laisuwannachart; Kaung Zaw; Piya Thongbang; Nining Istighosah; Putri Eka Sejati; Sunisa Chansaeng (Journal Of Nursing Practice, 2025)
Background: Adolescent alcohol consumption is a growing concern in Thailand. Suphan Buri Province has seen a sharper increase, from 0.01 to 0.09, highlighting regional challenges. Gaps in legislation and enforcement hinder efforts to address underage drinking effectively. This study uses the PRECEDE framework to explore socio-cultural and environmental factors, guiding targeted interventions for central Thailand. Purpose: The study aimed to identify the factors associated with alcohol consumption among senior high school students in Suphan Buri Province, Thailand. Methods: This cross-sectional study was conducted among senior high school students in Suphan Buri Province, Thailand, using a multi-stage sampling method to select 364 participants. Data were collected through an online self-administered questionnaire between February and March 2021. Descriptive statistics and Chi-Square tests were employed for data analysis, with the significance level set at p < .05. The questionnaire demonstrated strong validity (IOC: 0.67–1.00) and reliability, with Cronbach's Alpha scores of 0.885 for attitudes, 0.911 for media influence, 0.947 for peer conformity, and 0.978 for behavior. Results: The study analyzed 364 participants (51.1% male, 48.9% female) with an average age of 16.9 years. Most students (63.2%) had a GPA of 3.00–4.00. Alcohol consumption behavior was moderate (X̄ = 3.30, S.D. = 1.08), with the highest mean score for driving after drinking (X̄ = 3.57, S.D. = 1.32). Chi-Square analysis revealed significant associations between alcohol consumption and age, academic year, attitudes (predisposing factors), media influence (enabling factor), and peer conformity (reinforcing factor) at p < .05. Conclusion: The findings underscore the influence of age, educational level, attitudes, alcohol media and advertising influence, and peer conformity on alcohol consumption among senior high school students. These insights can guide the development of targeted prevention programs aimed at reducing alcohol use and associated risks in this population.